A comparison of metaheuristics algorithms for combinatorial optimization problems. application to phase balancing in electric distribution systems - Schweickardt, Gustavo Alejandro; Miranda, V.; Wiman, G. (Planta Piloto de Ingeniería Química, 2011)
Fil: Schweickardt, Gustavo Alejandro. Fundacion Bariloche. Instituto de Economia Energetica; Argentina. Comision Nacional de Energia Atomica. Gerencia del Area de Investigaciones y Aplicaciones no Nucleares. Gerencia de Fisica (CAB); Argentina